More Than Medals A History of the Paralympics and Disability Sports in Postwar Japan - Frost, Dennis J. (Cornell University Press, 2022)
How does a small provincial city in southern Japan become the site of a world-famous wheelchair marathon that has been attracting the best international athletes since 1981? In More Than Medals, Dennis J. Frost answers this question and addresses the histories of individuals, institutions, and events-the 1964 Paralympics, the FESPIC Games, the Ōita International Wheelchair Marathon, the Nagano Winter Paralympics, and the 2021 Tokyo Summer Games that played important roles in the development of disability sports in Japan. Sporting events in the postwar era, Frost shows, have repeatedly served as forums for addressing the concerns of individuals with disabilities. More Than Medals provides new insights on the cultural and historical nature of disability and demonstrates how sporting events have challenged some stigmas associated with disability, while reinforcing or generating others. Frost analyzes institutional materials and uses close readings of media, biographical sources, and interviews with Japanese athletes to highlight the profound-though often ambiguous-ways in which sports have shaped how postwar Japan has perceived and addressed disability. His novel approach highlights the importance of the Paralympics and the impact that disability sports have had on Japanese society. Open access edition funded by the National Endowment for the Humanities.